Answer:
x²+6x+9=0
x²+3x+3x+9=0
x(x+3)+3(x+3)=0
(x+3)(x+3)=0
either
x+3=0
x=-3
or
x+3=0
x=-3
Step-by-step explanation:
next method
x²+6x+9=0
x²+2×x×3+3²=0
it is in formula of (x+y)²
(x+3)²=0
x+3=√0
x+3=0
x=-3
Answer:
-30
Step-by-step explanation:
move and divide -3/5 to the right side
-3/5x = 18
x=18÷(-3/5)
x= -30
Unless you're given the value of the variables, you can't really solve for anything. The only thing you can do is simplify.
<span>39+5h+4g-2h
The only like terms are 5h and -2h.
39 + 3h + 4g
This would be the simplified version.</span>